Risks and side-effects of German and European return policy: Foreign policy, security and development trade-offs - Nadine Biehler; Anne Koch; Amrei Meier (Stiftung Wissenschaft und Politik (SWP), 2021)
Returning migrants without legal residence status to their countries of origin is high on the political agenda of Germany and the European Union. As well as seeking to increase the number of returns, policy efforts in this area also serve a symbolic function: They demonstrate that the state is upholding the rule of law and are regarded as an important means for stemming the growing popularity of political parties of the extreme right. In practice it is difficult to enforce the obligation to leave. Across Europe, governments succeed in only about one-third of cases. The lack of cooperation by countries of origin is regarded as one of the central reasons for this. The European Union is currently witnessing dynamic developments in the internal and external dimensions of return policy. The objective is to improve cooperation with countries of origin and make European processes more effective. The development, foreign policy and security costs associated with ongoing efforts to increase the number of returns are often not adequately accounted for. For example pressure to cooperate on readmissions can endanger democratic transition processes in countries of origin and weaken European bargaining power in other areas. The study calls for a comprehensive cost/benefit analysis of return policy that addresses these potential trade-offs in a systematic manner - and that provides the basis for pragmatic discussions about alternatives to return.
Keywords: 320